2008
DOI: 10.1080/09638280701622929
|View full text |Cite
|
Sign up to set email alerts
|

Unmet needs and health care utilization in young adults with cerebral palsy

Abstract: Although young adults with CP frequently receive treatment from health care professionals, they indicate unmet needs with respect to several areas such as information on diagnosis, functional mobility and formal health care. In the treatment of young adults with CP, attention should be paid to these aspects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
79
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(87 citation statements)
references
References 34 publications
7
79
1
Order By: Relevance
“…If it is true that those in the greatest need are also those with the most unmet needs and if a society is judged by how it serves its most needy, then a fuller examination of unmet needs could be very revealing. One expression of unmet need among high users may be the coincident utilization of alternative and self-help approaches to complement or supplement the shortcomings of mainstream healthcare (Donnelly et al 2007;Nieuwenhuijsen et al 2008). …”
Section: Discussionmentioning
confidence: 99%
“…If it is true that those in the greatest need are also those with the most unmet needs and if a society is judged by how it serves its most needy, then a fuller examination of unmet needs could be very revealing. One expression of unmet need among high users may be the coincident utilization of alternative and self-help approaches to complement or supplement the shortcomings of mainstream healthcare (Donnelly et al 2007;Nieuwenhuijsen et al 2008). …”
Section: Discussionmentioning
confidence: 99%
“…In group A and B in 2009, 70% of the participants with CP were ambulators with or without assistive devices compared with 78% in a Norwegian study (Jahnsen et al 2004b) and 76% in a Dutch study Scandinavian Journal of Disability Research 259 (Nieuwenhuijsen et al 2008). People with intellectual disabilities were not included in any of these studies.…”
Section: Mobilitymentioning
confidence: 90%
“…A Swedish qualitative study (Whitaker 2008) showed that parents are caregivers even if their disabled children are adults and have personal assistants. A Dutch study (Nieuwenhuijsen et al 2008) of adults (aged 16Á40) with CP found that 52% of the whole group and 90% of those with a severe disability met with a rehabilitation physician regularly. Almost three quarters of the participants had used allied health care at least once in the past year.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recruitment process of these studies has been described in detail elsewhere (Fig 1). [9][10][11][12] In short, eligible patients had a clinical diagnosis of CP. Patients were excluded when they were diagnosed with additional diseases or disorders affecting motor functioning and when they or their caregiver lacked a basic knowledge of the Dutch language.…”
Section: Design and Subjectsmentioning
confidence: 99%